Reflections on Equity in Higher Education: Are We Transforming Relationships? - Blackett, Adelle (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
This essay—originally delivered to the Canadian Association for the Prevention of Discrimination and Harassment in Higher Education—reflects on the ambivalent relationship between equity, diversity, and inclusion, and employment equity, canvassing both the existing literature on effectiveness and the normative imperative of achieving substantive equality. It also critically considers the vision embodied in one recent sector-specific initiative, the Scarborough Charter on Anti-Black Racism and Black Inclusion in Canadian Higher Education. It asks what frameworks enable us to prioritize the work of transforming relationships in higher education in Canada, and beyond.